Tape-disc-loop-mediated isothermal amplification (TD-LAMP) method as noninvasive approach for diagnosis of cutaneous leishmaniasis caused by L. tropica - Yasaman Taslimi; Sima Habibzadeh; Vahid Mashayekhi Goyonlo; Amin Akbarzadeh; Zahra Azarpour; Safoora Gharibzadeh; Mehrdad Shokouhy; Josefine Persson; Ali M. Harandi; Amir Mizbani; Sima Rafati (Heliyon, 2023)
Cutaneous leishmaniasis (CL) is a parasitic disease caused by the bite of infectious female sand flies with high socioeconomic burdens. There is currently no non-invasive, point-of-care, diagnostic method with high sensitivity and specificity available for CL. We herein report the development of a non-invasive tape disc (TD) sampling method combined with a loop-mediated isothermal amplification (LAMP) assay using primer sets targeting kinetoplast DNA (kDNA) of Leishmania tropica (L. tropica) with a colorimetric readout for species-specific diagnosis of CL. We tested our Tape-Disc (TD)-LAMP method on a panel of skin samples collected by TD from 35 confirmed L. tropica patients, 35 healthy individuals and 35 patients with non-L. tropica infections. The detection limit of the TD-LAMP assay was determined as 1 fg (fg), and the assay sensitivity and specificity of 97 % and 100 % for L. tropica infection, respectively. This non-invasive, sensitive and rapid diagnostic method warrants further exploration of its use for differential diagnosis of CL in disease endemic settings.